Kontribusi Kreativitas Belajar dan Disiplin Belajar Terhadap Prestasi Belajar Akuntansi Sektor Publik Mahasiswa Pendidikan Akuntansi Angkatan 2013 Universitas Muhammadiyah Surakarta - WAHYUNI, WAHYUNI; , Dr. Hj. Suyatmini, SE., M.Si (2015)
The purpose of this study were: 1) To determine the contribution of creativity to learn to achievement bealajar public sector accounting student Accounting FKIP force in 2013 Universitas Muhammadiyah Surakarta; 2) To determine the contribution of the discipline of learning to learning achievement in the public sector accounting student Accounting FKIP force in 2013 Universitas Muhammadiyah Surakarta; 3) To determine the contribution of creativity and discipline of learning to learn together on the learning achievement of public sector accounting in the Accounting class of 2013 student FKIP Muhammadiyah University of Surakarta. This research is a quantitative associative. The population in this study were all students of Accounting Education class of 2013 who took Public Sector Accounting courses totaling 184 students with a sample of 119 students were taken by proportional random sampling technique. Data obtained by using questionnaires and methods of documentation. The questionnaire has been previously tested by using validity and reliability as many as 20 students. Data analysis technique used is multiple linear regression analysis, t test, F test, test R2 and the relative contribution and effective. Results from the analysis of data obtained by a linear line equation Y = 21.730 + 0,598X1 + 0,456X2. The conclusion that can be drawn from this research are: 1) no contribution of creativity to learn to learning achievement Public Sector Accounting Accounting Education Student t test force, 2013. Based on the obtained t> t table, namely 3.229> 1.981 (α = 5%) and a significant value <0 , 05 is 0.002; 2) No contribution to the discipline of learning to learning achievement Public Sector Accounting Accounting Education Student t test force, 2013. Based on the obtained t> t table, namely 2.163> 1.981 (α = 5%) and the significance of <0.05 is 0.033; 3) there is the contribution of creativity and discipline of learning to learn together on learning achievement Public Sector Accounting Accounting Education Student force F 2013. Based on test results obtained Fhitung> Ftable is 20.475> 3.074 at 5% significance; 4) variable X1 relative contribution of 61.178% and 16.178% effective contribution, X2 gives the relative contribution of 38.063% and the effective contribution of 9.934%. R2 calculation results obtained 0.261, meaning 26.1% achievement of students affected by learning creativity and discipline of study, while the remaining 73.9% is influenced by other variables not examined in this study.